Primary mediastinal choriocarcinoma presenting as cutaneous metastasis with resistance to chemotherapy: case report and literature review - Khaled A. Murshed (14151927) (2020)
Cutaneous metastases of choriocarcinoma are rare. They may indicate poor prognosis and resistance to chemotherapy. In this report, we present a case of a 25-year-old man who presented with central pleuritic chest pain and right upper arm mass for about a week. The patient also had significant weight loss during the last 5 months along with an episode of generalized seizure. Chest computed tomography scan revealed an 8 cm anterior mediastinal mass. A skin punch biopsy from the right upper arm mass revealed a malignant neoplasm with morphology consistent with metastatic choriocarcinoma. Further work-up revealed multiple lung and brain lesions. Ultrasound of the testes revealed no abnormalities. Several chemotherapy regimens were tried; however, there was no response and the disease showed progression. The patient died 6 months after initial presentation. Other Information Published in: Journal of Cutaneous Pathology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/cup.13777